GSTPi-positive tumour microenvironment-associated fibroblasts are significantly associated with GSTPi-negative cancer cells in paired cases of primary invasive breast cancer and axillary lymph node metastases - Chaiwun B. (2017)
Background: Glutathione S-transferase Pi (GSTPi) expression is one of the factors, which is known to be associated with development of resistance to chemotherapeutics in cancer patients, including those with breast cancer. Yet, its expression has been reported to be undetectable in cancer cells in high percent of patients with primary breast cancer. However, GSTPi expression in stromal cells in breast tumour microenvironment, namely cancer-associated fibroblast (CAF), which is recognised to have major roles in cancer progression, remains poorly reported. Methods: The aim of the study was to determine the expression of GSTPi; vimetin, a fibroblast-associated cytoskeleton protein; and α-smooth muscle actin (α-SMA), a known marker of CAF in breast cancer tissue, by immunohistochemical staining method in consecutive histologic sections of formalin-fixed and paraffin-embedded tissue biopsy specimens from a cohort of 39 paired cases of patients with invasive breast cancer and the corresponding axillary lymph nodes metastases. Results: Ductal and acinar luminal epithelial cells, myoepithelial cells and surrounding fibroblasts exhibited a homogeneous cytoplasmic reactivity with anti-GSTPi antibody in 11 of 11 cases of benign breast tissue biopsies. The vimentin-positive fibroblasts were unreactive with anti-α-SMA antibody. Loss of GSTPi expression was observed in breast cancer cells, at both the primary and metastatic sites, in 31 of 39 paired cases, as compared with benign breast epithelial cells (Fisher's exact test P < 0.001). A significant association was observed between GSTPi-positive, vimentin-positive and α-SMA-positive fibroblast in tumour microenvironment at both sites. Conclusion: This is an original report of demonstration of a significance association between tumour microenvironment- associated GSTPi-positive CAF (vimentin/α-SMA-positive) and the GSTPi-negative cancer cells in paired cases of primary invasive breast cancer and the corresponding axillary lymph nodes metastases. © 2011 Cancer Research UK All rights reserved.